2008
DOI: 10.1177/0898010107311275
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Students' Perceptions of a Holistic Nursing Conference

Abstract: Themes suggested that nursing students gained knowledge about holistic nursing and felt empowered through personal interactions with national holistic nursing leaders. They felt motivated to incorporate holistic nursing principles into practice and self-care. In addition, they expressed an appreciation for the importance of lifelong learning and maintaining clinical competency through attendance at a professional conference. IMPLICATIONS FOR EDUCATION: Nursing students' attendance at a holistic nursing profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The findings of this study were similar to the findings of a previous study conducted by the same research team (Christiaens et al, 2008). In the previous study, student perceptions of attending the AHNA annual conference included empowerment, an appreciation for self-care and lifelong learning, and gaining more knowledge about holistic nursing.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings of this study were similar to the findings of a previous study conducted by the same research team (Christiaens et al, 2008). In the previous study, student perceptions of attending the AHNA annual conference included empowerment, an appreciation for self-care and lifelong learning, and gaining more knowledge about holistic nursing.…”
Section: Discussionsupporting
confidence: 88%
“…For the past 3 years, nursing students from a large private university have attended the AHNA annual conference with two faculty members. In 2007, the students wrote about their experiences and perceptions of the conference (Christiaens, Abegglen, & Rowley, 2008). Their journals revealed that conference attendance made them feel empowered, instilled the value of self-care, and taught them how to apply holistic nursing principles to practice.…”
Section: Introductionmentioning
confidence: 99%
“…They believed they had ''permission'' to perform self-care so they could be more effective caregivers. 24 These data are important, as it provides information about this new generation of nurses and their commitment not only to the profession, but also to themselves.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Global health conferences are forums of decision making, knowledge exchange, networking and personal development, pivotal to the field. 1 2 Health conferences provide opportunities that are highly beneficial for career development [3][4][5][6] and attendees from low-and middle-income countries (LMICs), regions disproportionately burdened by disease, unquestionably have much to contribute and to gain from active participation at these conferences. However, inequities in conference attendance, raised in recent opinion pieces, have drawn light to an area that requires critical attention.…”
Section: Introductionmentioning
confidence: 99%